"Environment and Ethics: A Philosophical Foundation for the Principle of Sustainability" (Comprehensive Journal of Science, 2025)
This study, entitled “Environment and Ethics: A Philosophical Foundation for the Principle of Sustainability”, seeks to explore the ethical and philosophical underpinnings of sustainability as more than a technical or economic concept. The research highlights a major gap in contemporary environmental policies: while they often emphasize technological and financial solutions, they largely neglect the normative values necessary for long-term commitment to sustainable practices. Using a descriptive-analytical and normative philosophical method, and relying on secondary sources such as philosophical literature, international reports, and ethical writings, the study examines key currents in environmental thought—including anthropocentrism, biocentrism, deep ecology, and the Gaia hypothesis. The findings reveal that sustainability requires an integrated moral framework based on principles of justice, responsibility, moderation, and stewardship. The study concludes with recommendations to embed these ethical principles into education, policymaking, institutional regulations, and public awareness initiatives, in order to bridge the gap between theory and practice and to promote a culture of sustainability across generations.
Keywords: environment, philosophy, sustainability.